Quality of Life at Work: the case of penitentiary agents in a Temporary Detention Center in Rio Grande do Norte (Research, Society and Development, 2017)
Prison officers, due to the nature of their profession, are subject to various factors of risk, tension, physical and mental exhaustion. This study is a research carried out at a Provisional Detention Center (CDP) in Rio Grande do Norte (RN), with the objective of analyzing Quality of Life at Work (QWL), as perceived by prison The model of Walton (1973). The method adopted was a field research, of an exploratory and descriptive character where the data were collected through a questionnaire with structured and closed questions. Allied to the "Quality of Life at Work Scale" according to the Walton model, adapted and proposed by Timossi et al (2009). The target population were the penitentiary agents servants of a RN's CDP. For this collection, the ethical care was adopted, through the letter of agreement of the institution and endorsement of the participants. The theoretical assumptions of this work are based on the studies of Walton (1973) that can be considered as the precursor of a scientific approach to QVT. For Walton, QVT depends closely on the balance between work and other spheres of life, the social role of the organization and the importance of reconciling productivity with QWL. In the analysis of the results it was observed a division by parts of the participants of the research, in which among the dimensions considered satisfactory, we have: the use and development of capacities; The social integration in the organization and the constitutionalism. On the other hand there was dissatisfaction with fair and adequate compensation; work conditions; Opportunity for growth and safety and the social relevance of life at work. It is observed that the QVT is affected by the subjectivity of the perception that each person has in relation to each dimension presented on their personal and professional aspirations in front of the organizational objectives. Some actions are suggested to improve the perception of QWL at work, such as the implementation of a Career Plan, career and salaries and the improvement of the physical environment and the safety of workers.